Effectiveness of Using Read-Ask-Put (RAP) Strategy in Reading Comprehension in the Reading for Enjoyment Course of the Second-Semester Students of the English Language Education Department at UHN I Gusti Bagus Sugriwa - Ni Wayan Chyntia Wulandari; Ni Wayan Satri Adnyani; Putu Santi Oktarina (Educational Journal, 2026)
This research aimed to determine whether students who learn using the Read-Ask-Put (RAP) Strategy achieve better reading comprehension scores than those who learn using the Discovery Learning strategy in the Reading for Enjoyment course of the second semester students of the English Language Education Department at UHN I Gusti Bagus Sugriwa. The design used was a quasi-experimental design, especially non-equivalent control-group design. The sample of this research was 38 students of the second-semester English Language Education Department that was chosen using convenience sampling technique. The data collection technique included pre-test, treatment, and post-test. The data were analyzed using the Quade ANCOVA in SPSS 26 version. The results showed that pre-test mean score of the experimental group was 86.48 and the post-test was 94.29. Meanwhile, the pre-test mean score of the control group was 80 and the post-test was 88.24. The hypothesis testing result showed the value of Sig. (1-tailed) = 0.320 > 0.05 which meant the null hypothesis (Ho) was accepted and the alternative hypothesis (Ha) was rejected. In conclusion, the students who learned using the Read-Ask-Put (RAP) strategy do not achieve better reading comprehension scores than the students who learned using the Discovery Learning strategy.